The Rhyme of History : Lessons of the Great War - MacMillan, Margaret, 1943- (Brookings Essay., 2013)
As the 100th anniversary of World War I approaches, historian Margaret MacMillan compares current global tensions-rising nationalism, globalization's economic pressures, sectarian strife, and the United States' fading role as the world's pre-eminent superpower-to the period preceding the Great War. In illuminating the years before 1914, MacMillan shows the many parallels between then and now, telling an urgent story for our time. THE BROOKINGS ESSAY: In the spirit of its commitment to high-quality, independent research, the Brookings Institution has commissioned works on major topics.